Cardiorespiratory treatments as modifiers of the relationship between particulate matter and health: A case-only analysis on hospitalized patients in Italy - Conti, Sara; Lafranconi, Alessandra; Zanobetti, Antonella; Fornari, Carla; Madotto, Fabiana; Schwartz, Joel; Cesana, Giancarlo (Environmental research, 2015)
A few panel and toxicological studies suggest that health effects of particulate matter (PM) might be modified by medication intake, but whether this modification is confirmed in the general population or for more serious outcomes is still unknown. We carried out a population-based pilot study in order to assess how pre-hospitalization medical treatments modify the relationship between PM<10μm in aerodynamic diameter (PM10) and the risk of cardiorespiratory admission. We gathered information on hospitalizations for cardiorespiratory causes, together with pre-admission pharmacological treatments, that occurred during 2005 in seven cities located in Lombardy (Northern Italy). City-specific PM10 concentrations were measured at fixed monitoring stations. Each treatment of interest was analyzed separately through a case-only approach, using generalized additive models accounting for sex, age, comorbidities, temperature and simultaneous intake of other drugs. Analyses were stratified by season and, if useful, by age and sex. Our results showed a higher effect size for PM10 on respiratory admissions in subjects treated with theophylline (Odds Ratio (OR) of treatment for an increment of 10μg/m3 in PM10 concentration: 1.119; 95% Confidence Interval (CI): 1.013–1.237), while for cardiovascular admissions treatment with cardiac therapy (OR: 0.967, 95% CI: 0.940–0.995) and lipid modifying agents (OR: 0.962, 95% CI: 0.931–0.995) emerged as a protective factor, especially during the warm season. Evidence of a protective effect against the pollutant was found for glucocorticoids and respiratory admissions. Our study showed that the treatment with cardiac therapy and lipid modifying agents might mitigate the effect of PM10 on cardiovascular health, while the use of theophylline seems to enhance the effect of the pollutant, possibly due to confounding by indication. It is desirable to extend the analyses to a larger population. •We carried out a pilot study in Northern Italy using administrative databases.•We retrieved data on cardiorespiratory hospitalizations and drug prescriptions.•We evaluated how pre-hospitalization treatments modify the effect of PM10.•Cardiac therapy and lipid modifying agents might mitigate the effect of PM10.•Subjects treated with theophylline seem more susceptible to the effect of PM10.